Hydnum khanspurense sp. nov. and H. berkeleyanum from Pakistan - Ali, Muhammad; Ghafoor, Aneeqa; Ghafoor, Annie; Niazi, Abdul Rehman; Swenie, Rachel A. (Phytotaxa, 2024)
During mushroom surveys (2017 to 2022) of moist temperate forests of Pakistan, five different collections of Hydnum were found. Morpho-anatomical and phylogenetic analysis of the internal transcribed spacer (nrITS) of these specimens revealed one species new to science (Hydnum khanspurense sp. nov.) and one new record for Pakistan (Hydnum berkeleyanum). Hydnum khanspurense sp. nov. is characterized by non-decurrent spines, relatively smaller basidiospores and basidia with 1–4 sterigmata, along with ITS region divergence from the closest related species of subgenus Pallida, H. pallidomarginatum and H. flabellatum. Similarly, H. berkeleyanum, a member of subgenus Hydnum, was confirmed for the first time in Pakistan on the basis of micro-morphological and phylogenetic analysis. Detailed phylogenetic analysis confirming their systematic positions and morpho-anatomical studies of these taxa are provided and illustrated.